Lessons learned from three university experiments onboard the REXUS/BEXUS sounding rockets and stratosphere balloons - Sinn, Thomas; Brown, Roy; McRobb, Malcolm; Wujek, Adam; Lowe, Christopher; Weppler, Johannes; Parry, Thomas; Yarnoz, Daniel Garcia; Brownlie, Fraser; Skogby, Jerker; Dolan, Iain; Querioz, Tiago de França; et al. (2013)
Over the last three years the authors have been involved in three experiments that were or will be launched on sounding rockets and high altitude balloons with the REXUS/BEXUS program (Rocket-borne / Balloon-borne Experiments for University Students). The first experiment, called Suaineadh was launched from Esrange (Kiruna, Sweden) onboard REXUS 12 in March 2012. Suaineadh had the purpose of deploying a web in space by using centrifugal forces. The payload was lost during re-entry but was recovered 18 month later in early September 2013. StrathSat-R is the second experiment, which had the purpose of deploying two cube satellites with inflatable structures from the REXUS 13 sounding rocket, was launched first in May 2013 and will be launched a second time in spring 2014. The last experiment is the iSEDE experiment which has the goal of deploying an inflatable structure with disaggregated electronics from the high altitude balloon BEXUS15/16 in October 2013. All these experiments have been designed, built and flown in a timeframe of one and a half to two years. This paper will present the lessons learned in project management, outreach, experiment design, fabrication and manufacturing, software design and implementation, testing and validation as well as launch, flight and post-flight. Furthermore, the lessons learned during the recovery mission of Suaineadh will be discussed as well. All these experiments were designed, built and tested by a large group of university students of various disciplines and different nationalities. StrathSat-R and iSEDE were built completely at Strathclyde but the Suaineadh experiment was a joint project between Glasgow and Stockholm which was especially tricky during integration while approaching the experiment delivery deadline. This paper should help students and professionals across various disciplines to build and organise these kinds of projects more efficiently without making the same, sometimes expensive, mistakes all over again.